Comparative performance of Convolutional Neural Networks Architecture for face biometric authentication system - Mat Ariff, Noor Azwana; Ismail, Amelia Ritahani; Abdul Aziz, Normaziah (IEEE, 2021)
Biometric authentication plays a vital role nowadays compared to password or token-based authentication. There are a lot of methods for biometric authentication algorithms that have been proposed but it can be said that the Deep Learning method give much more reliable and secure compared to other methods specifically Convolutional Neural Networks (CNN) for face recognition. Therefore, this paper will review the performance of top CNN architectures which are LeNet, AlexNet, VGGNet, GoogleNet, and ResNet by using the proposed face dataset of 7 celebrity classes where each class has 35 images that have been collected from Google Images. Data augmentation has been performed to increase the size of the dataset before it was fed into the CNN model. The experiment shows that AlexNet shows promising results compared to the other architectures on the proposed dataset.